Clinical Chemistry, Immunology and Laboratory Quality Control A Comprehensive Review for Board Preparation, Certification and Clinical Practice - Dasgupta, Amitava Wahed, Amer (Elsevier, 2014)
All pathology residents must have a good command of clinical chemistry, toxicology, immunology, and laboratory statistics to be successful pathologists, as well as to pass the American Board of Pathology examination. This book presents core topics and detailed case studies that illustrate the application of clinical chemistry knowledge to everyday patient care and offers practical examples of how things function in the pathology clinic.